"Everything is changed by virtue of being lost": African Futurism Between Globalization and the Anthropocene in Tade Thompson's Rosewater. Issue 1 (March 2020) - O'Connell, Hugh Charles
Abstract : This essay examines Tade Thompson's 2016 novel Rosewater as an exploration of political and environmental apocalypse, and what, invoking Jacques Derrida by way of Walter Benjamin, I am going to argue for as a weak utopianism: a utopicity without utopianism. Thompson's novel refashions and enervates a number of sf tropes: cyberpunk, first contact, invasion and apocalypse, and alien-human symbiosis, among others. Yet, despite the energy catalyzed by this generic hybridity, the novel is ultimately permeated by loss: lost objects, missing persons, nations that "go dark" and remove themselves from the global world-system, and most significantly, the determinate and impending loss of the Earth and humanity. In short, what is finally lost is any sense of the future. Intervening in a number of related discourses—African sf, Africanfuturism, and African-utopianism—what I find of most interest, as my title suggests, is the way that Thompson's novel wrestles with futurity at a time when so many potential futures seem to be annulled by the twinned forces of economic globalization and the Anthropocene.